The Pursuit of External Knowledge in Eco-Innovation. Analysis of the Agri-Food Sector in Spain (Journal of Business, Universidad del Pacífico (Lima, Peru), 2018)
The research about the search for opportunities through open cooperation strategies points to an exchange of knowledge among a certain number of sources, aimed at sustaining competitive advantage. From this new vision emerges the paradigm of open innovation, which has prompted a change in the organization of resources, information filtering, and rapid absorptive capacity. Awareness of climate problems and external societal pressures can motivate companies to create new technologies and new forms of cooperation to avoid environmental problems. Based on a survey of Spanish agri-food firms, we find that the depth of external sources of innovation increases environmental improvement in a U-shaped relationship.